Bryophyte-based full-microporous carbon as well as preparation method and application thereof

By using bryophytes as charcoal source, the preparation of full microporous carbon by potassium hydroxide impregnation and firing methods, the problems of unstable supply and complex structure of traditional biomass carbon materials are solved, and high-efficiency and low-cost high-rate capacitor storage are achieved The production of energy materials overcomes the insufficient production efficiency and uniformity of traditional biomass carbon materials.

CN119284901APending Publication Date: 2025-01-10CHONGQING COLLEGE OF ELECTRONICS ENG
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411415017.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Traditional biomass and biomass waste preparation carbon materials have high cost and efficiency limitations caused by unstable raw material supply, difficulty in collecting and transporting, structural diversification and inhomogeneity, and it is difficult to achieve large-scale high-value and efficient utilization.

Method used

Using bryophytes as charcoal source, the whole microporous charcoal was prepared by simple chopping, potassium hydroxide impregnation and protective atmosphere firing methods, overcoming the complexity and uncertainty of the raw material structure, and improving the charcoal through high water content characteristics and simple structure. Material uniformity and production efficiency.

Benefits of technology

A high uniformity, low cost bryophyte-based all-porous carbon has high specific surface area and pore capacity, suitable for large-scale production, used for high-speed capacitor energy storage materials, achieving high specific capacitance and capacitance retention, and is excellent In traditional biomass charcoal materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284901A_ABST
    Figure CN119284901A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of bryophyte-based full-microporous carbon. The preparation method comprises the following steps: 1) simply chopping bryophyte and then naturally airing the bryophyte; 2) dipping the naturally aired bryophyte in a potassium hydroxide solution, then fishing out and naturally airing again; (3) firing the soaked and naturally aired bryophyte in a protective atmosphere to obtain primary charcoal; and 4) washing the primary charcoal with a hydrochloric acid solution and water until the primary charcoal is neutral to obtain activated carbon with the micropore content of 100%, namely the bryophyte-based full-micropore charcoal. According to the preparation method, the bryophyte with high water content serves as a carbon source, the carbon material with the micropore content being 100% is obtained through firing, the produced carbon has the advantages of being large in specific surface area, high in pore volume, high in nitrogen and oxygen doping level and the like, and when the carbon is applied to the capacitive energy storage material, high specific capacitance can be kept under the high-rate charging and discharging conditions. The method provided by the invention has the advantages of stable raw material supply, low raw material and production cost, simplicity in operation and easiness in large-scale production when being used for producing the carbon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of electrode materials for capacitor energy storage, and specifically relates to a bryophyte-based fully microporous carbon and a preparation method and application thereof. Background Art

[0002] High-value utilization of biomass or biomass waste is an important way to develop a circular economy and a low-carbon economy. At present, people have made some progress in the utilization of some biomass or biomass waste. Among them, the use of biomass or biomass waste to prepare carbon materials for use in capacitor energy storage electrode materials is a widely studied high-value utilization approach. The use of biomass or biomass waste to prepare carbon materials not only increases the value of biomass and reduces the environmental pollution caused by the simple incineration of biomass waste, but also its special properties may produce some special application values ​​and have broad prospects. However, there are some inherent problems that are difficult to overcome in the use of traditional crop biomass or biomass waste such as wheat straw and straw to prepare carbon materials, which seriously limits its practical application.

[0003] First, most biomass and biomass waste are heavily dependent on agricultural production at the upper level, which makes them uncertain when they are used as raw materials. Agricultural production often has specific seasonal characteristics, which makes the supply of biomass resources naturally unstable. Its supply is often only produced at very few times a year. For enterprises to achieve a stable supply of raw materials, they must purchase, transport and store them in large quantities during the short harvest season. This leads to problems and difficulties in capital occupation, storage sites, fire safety, environmental protection and other aspects of enterprises; second, biomass and biomass waste are mainly produced in vast and scattered agricultural areas, and effective collection and transportation are extremely difficult. Under the current agricultural production model, it is still a difficult task to transport agricultural waste from the fields to a location where it can be transported by road, and the human resources required are often difficult to obtain or the cost is huge. In addition, the cost of transporting biomass and biomass waste from the production area to the processing enterprise is often high, which seriously limits the actual production benefits; third, biomass naturally has structural diversity and uneven characteristics, which makes large-scale utilization difficult. Most biomass and biomass waste are higher plants with clear physiological structure distinctions such as stems, leaves, and roots. This also leads to large differences in the microscopic cells and physical structure characteristics of each part. The carbon materials prepared from them are not highly uniform in properties and are difficult to meet the more demanding high-rate energy storage needs. However, if further sorting is carried out, it will lead to increased costs. For this reason, although there are currently many studies on the preparation of carbon materials from biomass or biomass waste, non-technical limitations in actual production still seriously restrict their large-scale, high-value and efficient utilization.

[0004] There are no reports on the use of mosses as biomass charcoal sources. Currently, most of the mosses obtained from nature are discarded except for a small amount. Their use is mainly for landscape construction, and there is a lack of more high-value utilization methods. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a bryophyte-based fully microporous carbon and a preparation method thereof, aiming to solve the problem that it is difficult to achieve large-scale efficient production when preparing carbon materials from traditional biomass and biomass waste. The present invention also provides the use of the bryophyte-based fully microporous carbon in high-rate energy storage materials.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] A method for preparing bryophyte-based fully microporous carbon comprises the following steps:

[0008] 1) Chop the moss plants into small pieces and dry them naturally;

[0009] 2) dipping the naturally dried bryophytes in a potassium hydroxide solution, then taking them out and drying them naturally again;

[0010] 3) firing the impregnated and naturally dried moss plants under a protective atmosphere to obtain primary charcoal;

[0011] 4) The primary carbon is washed with hydrochloric acid solution and water until it becomes neutral, thereby obtaining activated carbon with a micropore content of 100%, namely, moss-based fully microporous carbon.

[0012] In some specific embodiments, the bryophyte in step 1) is one of the mosses of the genus Glauca in the family Glauca and the mosses of the genus Glauca in the family Glauca, or a mixture of the two.

[0013] In certain specific embodiments, the molar concentration of the potassium hydroxide solution in step 2) is 1-4 mol / L in terms of molar concentration.

[0014] In some specific embodiments, the immersion time in step 2) is 24-48 hours.

[0015] In some specific embodiments, the firing process in step 3) is: heating from room temperature to 400-500 degrees Celsius and maintaining for 2-4 hours, then continuing to heat to 700-750 degrees and maintaining for 2-4 hours, and then cooling to room temperature.

[0016] In some specific embodiments, the protective atmosphere in step 3) is one of nitrogen or argon.

[0017] The bryophyte-based fully microporous carbon prepared by the aforementioned preparation method has a micropore content of 100%.

[0018] A use of the aforementioned bryophyte-based fully microporous carbon in an electrode material for high-rate capacitor energy storage.

[0019] Compared with the prior art, the present invention has at least the following advantages:

[0020] 1) The preparation method of the moss-based fully microporous carbon provided by the present invention is the first time that the inventor uses moss as a carbon source. Moss is the lowest higher plant with a simple structure, consisting of only two parts: stems and leaves. Some mosses only have flat thallus without real roots and vascular bundles. Therefore, moss often has a highly consistent biological microstructure, which can overcome the problem of overly complex microstructures. Therefore, when using moss to prepare carbon materials, it is possible to obtain products with high uniformity. In addition, moss has a high water content because it contains a large number of macroporous structures inside, which have high wettability to water, so that it has a large number of microscopic water flow and evaporation biological structures, which can It can avoid the wettability problem caused by the size effect of other plants, and has the possibility of being used to prepare high-rate energy storage materials; secondly, the general reproduction method of moss plants is spore reproduction, which can be quickly, multi-layered, and artificially cultivated in large quantities near processing enterprises, and the planting density per unit area can be greatly improved; most mosses are also evergreen all year round, resistant to extensive management, extremely drought-resistant, and more suitable for growing on lighter organic substrates such as peat and sawdust. It can also greatly overcome the uncertainty and transportation problems of raw materials, making it a relatively perfect raw material for high-value utilization of biomass, and effectively solving the problem of difficulty in achieving large-scale efficient production when preparing carbon materials from existing traditional biomass and biomass waste.

[0021] 2) The preparation method provided by the present invention has easy-to-obtain raw materials, simple process, low production cost, and high repeatability, and is suitable for large-scale production and promotion; the prepared moss-based fully microporous carbon has a micropore content of 100%, and has the advantages of large specific surface area, high pore volume, high nitrogen and oxygen doping levels, etc. When it is applied to capacitor energy storage materials, it can achieve high specific capacitance under high-rate charge and discharge conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.

[0023] Figure 1 This is a SEM image of the bryophyte-based fully microporous carbon in Example 1 of the present invention;

[0024] Figure 2TEM image of the bryophyte-based fully microporous carbon in Example 1 of the present invention;

[0025] Figure 3 This is a pore structure diagram of the bryophyte-based fully microporous carbon in Example 1 of the present invention;

[0026] Figure 4 This is a charge and discharge curve of the bryophyte-based fully microporous carbon in Example 1 of the present invention at a current density of 1 A / g;

[0027] Figure 5 This is a charge and discharge curve of the bryophyte-based fully microporous carbon in Example 1 of the present invention at a current density of 100 A / g;

[0028] Figure 6 This is a SEM image of the bryophyte-based fully microporous carbon in Example 2 of the present invention;

[0029] Figure 7 TEM image of the bryophyte-based fully microporous carbon in Example 2 of the present invention;

[0030] Figure 8 This is a pore structure diagram of the bryophyte-based fully microporous carbon in Example 2 of the present invention;

[0031] Fig. 9 This is a charge and discharge curve of the bryophyte-based fully microporous carbon in Example 2 of the present invention at a current density of 1 A / g;

[0032] Fig.10 This is a charge and discharge curve of the bryophyte-based fully microporous carbon in Example 2 of the present invention at a current density of 100 A / g;

[0033] Fig.11 It is a curve diagram of the specific capacitance change of straw-based carbon at a current density of 0.5-20A / g in the comparative example of the present invention;

[0034] Fig.12 This is the pore structure distribution diagram of the straw-based carbon in the comparative example of the present invention. DETAILED DESCRIPTION

[0035] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0036] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values ​​with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values ​​listed herein include the endpoints of the range, and all integers and fractions within the range.

[0037] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.

[0038] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.

[0039] Example 1

[0040] This embodiment provides a method for preparing bryophyte-based fully microporous carbon, which comprises the following steps:

[0041] 1) Using fresh moss with high water content collected from the wild in a certain city in the southwest as raw material, simply washing it with water to remove the mud and sand, cutting it into segments with a size of less than 1 cm, and drying it under natural ventilation for 15 days to obtain dried moss;

[0042] 2) Prepare a 2 mol / L potassium hydroxide solution, and completely immerse the dried moss in the solution for 24 hours, with a liquid-to-solid ratio of 20 L / kg, and stir for 5 minutes every 2 hours to fully immerse the moss; after immersion, remove the moss and place it in a container to dry naturally again; the potassium hydroxide solution after immersion can be used again after replenishment;

[0043] 3) The impregnated and naturally dried moss is placed in a muffle furnace protected by flowing nitrogen for firing, with a heating rate of 5°C / min during the firing process, and the temperature is kept constant at 450°C for 2 hours to remove tar from the moss and form a carbon skeleton; after the constant temperature is completed, the temperature is continuously raised to 750°C at a rate of 5°C / min and then maintained for 2 hours, so that potassium hydroxide etches micropores on the carbon skeleton, and after the constant temperature is completed, the temperature is lowered to room temperature at a rate of 3°C / min to obtain primary carbon;

[0044] 4) The primary carbon is washed in a dilute hydrochloric acid solution to remove ash, and then washed with deionized water until neutral, to finally obtain a bryophyte-based fully microporous carbon.

[0045] The present application conducts a performance test on the bryophyte-based fully microporous carbon prepared in this embodiment, specifically:

[0046] 1) Microstructure

[0047] In this example, the prepared bryophyte-based fully microporous carbon was subjected to microstructural testing, and its SEM image is shown in FIG. Figure 1 As shown in the figure, it can be seen that the obtained carbon material has a loose and porous structure, and its pores are interconnected; its TEM image is as follows Figure 2As shown in the figure, it can be seen that the material has a rich microporous structure and has the characteristics of nanosheets; such a microstructure can create a large number of active sites for ion adsorption, which is conducive to obtaining high specific capacitance performance. Further ICP test results show that the O element doping amount of the material is 11.3%, and the N element doping amount is 0.98%. Such doping is also conducive to creating more pseudocapacitance when the material is used as a capacitor energy storage material, which is conducive to obtaining higher specific capacitance performance.

[0048] 2) Pore structure test

[0049] In this example, the prepared bryophyte-based fully microporous carbon was tested for pore structure using an ASAP 2460 specific surface area and pore size analyzer. The specific surface area test results showed that the specific surface area of ​​the obtained carbon material was 1972 m 2 / g (BET method), total pore volume 0.76cm3 / g (NLDFT method). The pore size distribution results are as follows Figure 3 As shown in the figure, it can be seen that the pore size distribution of the carbon material is all below 2nm, that is, the porous carbon is a fully microporous carbon with a micropore content of 100%, and a large number of pores with a pore size distribution below 1nm. Such pore distribution characteristics are more conducive to obtaining a larger specific capacitance.

[0050] 3) Rate performance test

[0051] In this example, the prepared bryophyte-based fully microporous carbon was subjected to charge and discharge curve tests at current densities of 1 A / g and 100 A / g. The results are as follows: Figure 4 and Figure 5 As shown in the figure, it can be seen that the specific capacitance of 387F / g is achieved at a current density of 1A / g, and the specific capacitance is still maintained at a high level of 297F / g when the current density is increased to an ultra-high rate of 100A / g. When the current is provided at an ultra-high rate of 100 times, it still provides 76.7% of the capacitance retention, which fully meets the needs of high-rate capacitance energy storage and is better than most reported biochar materials.

[0052] Example 2

[0053] This embodiment 2 provides a method for preparing bryophyte-based fully microporous carbon, which comprises the following steps:

[0054] 1) Using fresh moss with high water content (commonly known as Duoduo moss) collected from the wild in a certain city in southwest China as raw material, simply washing it with water to remove the mud and sand, cutting it into blocks with a size of less than 1 cm, and drying it under natural ventilation and light for 15 days to obtain dried moss;

[0055] 2) Prepare 3 mol potassium hydroxide solution, immerse the dried moss completely in the solution for 24 hours, with a liquid-to-solid ratio of 20 L / kg, and stir for 10 minutes every 2 hours to ensure that the moss is fully immersed. After the immersion is completed, remove the moss and place it in a container to dry naturally again;

[0056] 3) The impregnated and naturally dried real moss is placed in a muffle furnace with flowing nitrogen for firing. During the firing process, the temperature is increased at a rate of 5°C / min and kept constant at 500°C for 2.5 hours to remove tar from the large gray moss and form a carbon skeleton; after the constant temperature is completed, the temperature is continuously increased to 700°C at a rate of 5°C / min and then maintained for another 2 hours, so that potassium hydroxide etches micropores on the carbon skeleton. After the constant temperature is completed, the temperature is lowered to room temperature at a rate of 4°C / min to obtain primary carbon;

[0057] 4) The primary carbon is washed in a dilute hydrochloric acid solution to remove ash, and then washed with deionized water until neutral, and finally a carbon material with a micropore content of 100% is obtained.

[0058] The present application conducts a performance test on the bryophyte-based fully microporous carbon prepared in this embodiment, specifically:

[0059] 1) Microstructure

[0060] In this example, the prepared bryophyte-based fully microporous carbon was subjected to microstructural testing, and its SEM image is shown in FIG. Figure 6 As shown in the figure, it can be seen that the obtained carbon material has a loose and porous structure, and its pores are interconnected; its TEM image is as follows Figure 2 As shown in the figure, it can be seen that the material has a rich microporous structure and has the characteristics of nanosheets; such a microstructure can create a large number of active sites for ion adsorption, which is conducive to obtaining high specific capacitance performance. Further ICP test results show that the O element doping content of the material is 9.1%, and the N element doping content is 1.4%. Such doping is also conducive to creating more pseudocapacitance when the material is used as a capacitor energy storage material, which is conducive to obtaining higher specific capacitance performance.

[0061] 2) Pore structure test

[0062] In this example, the prepared bryophyte-based fully microporous carbon was tested for pore structure using an ASAP 2460 specific surface area and pore size analyzer. The specific surface area test results showed that the specific surface area of ​​the obtained carbon material was 1547 m 2 / g (BET method), total pore volume 0.46cm 3 / g (NLDFT method). The pore size distribution results are as follows Figure 3As shown in the figure, it can be seen that the pore size distribution of the carbon material is all below 1.6nm, that is, the porous carbon is a fully microporous carbon with a micropore content of 100%, and a large number of pores with a pore size distribution below 1nm. Such pore distribution characteristics are more conducive to obtaining a larger specific capacitance.

[0063] 3) Rate performance test

[0064] In this example, the prepared bryophyte-based fully microporous carbon was subjected to charge and discharge curve tests at current densities of 1 A / g and 100 A / g. The results are as follows: Fig. 9 and Fig.10 As shown in the figure, it can be seen that the specific capacitance of 344F / g is achieved at a current density of 1A / g, and the specific capacitance is still maintained at a high level of 273F / g when the current density is increased to an ultra-high rate of 50A / g. At an ultra-high rate of 50 times the current, 79.36% of the capacitance retention is still provided, which fully meets the needs of high-rate capacitance energy storage and is better than most reported biochar materials.

[0065] Comparative Example

[0066] This comparative example provides an activated carbon, the preparation method of which is substantially the same as that of Example 1, except that the raw material used is rice straw;

[0067] The carbon material prepared in this comparative example was tested for rate performance, and the results are as follows: Fig.11 As shown in Figure 1, although the carbon material can provide a specific capacitance of more than 350F / g at a small current density below 1A / g, when the current density increases to more than 10A / g, the specific capacitance provided begins to be lower than 250F / g, and the capacitance retention rate is lower than 70%. The test results of its pore structure are as follows: Fig.12 As shown, it is shown that the pore size distribution of the carbon material is mainly concentrated between 2-6 nm, which belongs to a mesoporous carbon material, and is essentially different from the fully microporous carbon obtained in the embodiment provided by the present invention.

[0068] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and should all be included in the scope of the claims and specification of the present invention.

Claims

1. A method for preparing bryophyte-based fully microporous carbon, characterized in that: The steps include: 1) Chop the moss plants into small pieces and dry them naturally; 2) dipping the naturally dried bryophytes in a potassium hydroxide solution, then taking them out and drying them naturally again; 3) firing the impregnated and naturally dried moss plants under a protective atmosphere to obtain primary charcoal; 4) The primary carbon is washed with hydrochloric acid solution and water until it becomes neutral, thereby obtaining activated carbon with a micropore content of 100%, namely, moss-based fully microporous carbon.

2. The method for preparing bryophyte-based fully microporous carbon according to claim 1, characterized in that: The bryophyte in step 1) is one of the mosses of the genus Moss in the family Mossaceae and the mosses of the genus Moss in the family Mossaceae, or a mixture of the two.

3. The method for preparing bryophyte-based fully microporous carbon according to claim 1, characterized in that: In terms of molar concentration, the molar concentration of the potassium hydroxide solution in step 2) is 1-4 mol / L.

4. The method for preparing bryophyte-based fully microporous carbon according to claim 1, characterized in that: The immersion time in step 2) is 24-48 hours.

5. The method for preparing bryophyte-based fully microporous carbon according to claim 4, characterized in that: The firing process in step 3) is: heating from room temperature to 400-500 degrees Celsius and maintaining for 2-4 hours, then continuing to heat to 700-750 degrees and maintaining for 2-4 hours, and then cooling to room temperature.

6. The method for preparing bryophyte-based fully microporous carbon according to claim 4, characterized in that: The protective atmosphere in step 3) is one of nitrogen or argon.

7. A bryophyte-based fully microporous carbon prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The micropore content of the moss-based fully microporous carbon is 100%.

8. Use of the bryophyte-based fully microporous carbon according to claim 7 in an electrode material for high-rate capacitive energy storage.

Citation Information

Cited By

  • Directional activated modified charcoal based on green bristlegrass silicon-rich-vascular bundle structure, preparation method and application thereof

    CN121669176A